Reduced Graphene Oxide in Cathode Formulations Based on LiNi0.5Mn1.5O4. Issue 10 (11th August 2015) - Arbizzani, C.; Da Col, L.; De Giorgio, F.; Mastragostino, M.; Soavi, F.
Abstract : We investigated the electrochemical properties of composite cathodes obtained by mixing LiNi0.5 Mn1.5 O4 (LNMO), reduced graphene oxide (RGO) and carbon black (C65). Electrochemical electrode characterization was carried out in ethylene carbonate: dimethyl carbonate and 1 M LiPF6 by galvanostatic charge/discharge cycles up to 4.8 V vs. Li + /Li and impedance spectroscopy. We demonstrate that RGO improves the electrode/electrolyte interface stability at high potentials and, consequently, the cycling stability of LNMO cathodes in the presence of C65 with 92% capacity retention after 100 cycles at 1 C. The reciprocal effect of RGO and C65 is also beneficial for rate capability, which retained a specific capacity of 75 mAh g −1 at 10 C. The electric contact between particles is promoted by C65 ′ s conductive percolating network; RGO enhances the electrical conductivity of the composite electrode and hinders undesirable reactions between LNMO and the electrolyte. Despite RGO's lower electronic resistivity with respect to C65, the addition of RGO alone to LNMO is not sufficient to assure good performance. The mixing procedure without C65 promotes the agglomeration of graphene nanosheets rather than their distribution among LNMO particles and aggregates, limiting the electron and Li + transport in the cathode material.